“Fasten your seat belts”: Investigating learners’ perceptions regarding the implementation of tasks in an English online course - Trevisol, Juliane Regina; da Silva, Leonardo; Ferraz D'Ely, Raquel Carolina (Revista Investigações, 2019)
Considering the growth of distance education, this qualitative study investigated learners’ perceptions of the implementation of traveling-themed tasks (ELLIS, 2003) in a virtual course of English as a foreign language. The course was offered to university staff members for a semester. Four participants took part in it. Instruments were a consent form, two questionnaires, and a Skype interview. Results suggest learners perceived the course as motivating, noticing their task engagement from the perspective of “l’education integrale” (LONG, 2015) and “learning by doing”. Furthermore, learning was related to cultural aspects noticed, interesting sites, and the connection with previous traveling experiences.